Synthesis of Tetrahydroquinoline‐Embedded Bridged Benzothiaoxazepine‐1, 1‐dioxides. Issue 45 (30th November 2017) - Borgohain, Hemi; Devi, Runjun; Dheer, Divya; Borah, Biraj Jyoti; Shankar, Ravi; Das, Sajal Kumar
Abstract : A diastereoselective synthesis of previously unknown tetrahydroquinoline‐containing bridged benzothiaoxazepine‐1, 1‐dioxides is presented. The three‐step protocol uses readily available N ‐aryl‐2‐fluorobenzenesulfonamides and trans ‐2, 3‐epoxy‐cinnamyl‐alcohol‐derived tosylates as the starting materials, involves N ‐alkylation of sulfonamides, intramolecular epoxide ring‐opening, and SN Ar reactions as the reaction steps, and requires only one chromatographic purification to access the desired products in good overall yields. Abstract : Tetrahydroquinoline‐containing bridged benzothiaoxazepine‐1, 1‐dioxides are synthesized in a three‐step protocol, starting from readily available N ‐aryl‐2‐fluorobenzenesulfonamides and trans ‐2, 3‐epoxy‐cinnamyl‐alcohol‐derived tosylates. The method involves N ‐alkylation of sulfonamides, intramolecular epoxide‐ring‐opening, and SN Ar reactions. Only one chromatographic purification is required.